Coverage of Cervical Cancer Screening in Catalonia for the Period 2008–2011 among Immigrants and Spanish-Born Women - Rodriguez-Sales, Vanesa; Roura, Esther; Ibañez, Raquel; Peris, Mercè; Bosch, F. Xavier; De Sanjose, Silvia (Frontiers in Oncology, 2013)
Background: Female immigration in Catalonia, Spain, increased dramatically in the last 10 years. The Public Health system in the Region, provides a free of charge opportunistic cervical cancer screening. Aim: This study examines cervical cancer screening coverage and prevalence of cytology abnormalities in Catalonia by immigration status. Methods: The study analyzes the cytologies registered among women aged 25–65 that have been attended at the Primary Health Centers (PHC) for any reason (n = 1,242,230) during 2008–2011. Coverage was estimated from Governmental data base Information System Primary Care (SISAP) that includes 77% of PHC. The database is anonymous, and includes information on age, country of birth, diagnostic center, and cytology results. Results: During the period 2008–2011, 642,643 smears were performed in a total of 506,189 women over 14 years, of whom 18.3% were immigrants. Cytology coverage was higher among immigrant women compared to Spanish born (51.2 and 39% respectively). Immigrant women also had a higher prevalence of abnormal Paps compared to the Spanish population, 4.5 and 2.9% respectively (p < 0.001). Conclusion: Immigrant women in Catalonia had a high access to the Public Health Services and to cervical cancer screening facilities. The higher prevalence of abnormal cytologies in immigrant women compared to native women indicates the relevance to prioritize cervical cancer screening activities on a regular base in new comers.